Laws, Policies, and Collective Agreements Protecting Low-wage and Digital Platform Workers During the COVID-19 Pandemic. (November 2022) - MacEachen, Ellen; de Rijk, Angelique; Dyreborg, Johnny; Fassier, Jean-Baptiste; Fletcher, Michael; Hopwood, Pamela; Koivusalo, Meri; Majowicz, Shannon; Meyer, Samantha; Ståhl, Christian; Welti, Felix
In the context of the COVID-19 pandemic, this commentary describes and compares shifting employment and occupational health social protections of low-wage workers, including self-employed digital platform workers. Through a focus on eight advanced economy countries, this paper identifies how employment misclassification and definitions of employees were handled in law and policy. Debates about minimum wage and occupational health and safety standards as they relate to worker well-being are considered. Finally, we discuss promising changes introduced during the COVID-19 pandemic that protect the health of low-wage and self-employed workers. Overall, we describe an ongoing "haves" and a "have not" divide, with on the one extreme, traditional job arrangements with good work-and-health social protections and, on the other extreme, low-wage and self-employed digital platform workers who are mostly left out of schemes. However, during the pandemic small and often temporary gains occurred and are discussed.